(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. Provisioning is the process of setting aside an amount that may be necessary to settle a possible obligation when neither the amount nor the date of the obligation can be estimated with certainty. The objective of accounting and reporting in this area is to establish provisions and to choose the best option for making such provisions. Due to their dynamic nature, liabilities significantly affect the solvency of a business entity, require effective cash flow management and control over the actual status of settlements. The purpose of this article is to study the main aspects of recognising collateral, covering domestic and international accounting and reporting practices. Methods. In the course of the study, the following methods were used: monographic method for studying the literature on the recognition of collateral; method of regulatory support for assessing the established rules and regulations on collateral; analytical method for analytical assessment of the justification of collateral. Results. The creation of collateral is a necessity determined by current legislation and regulations. However, the list of collateral provided in National Accounting Standards 11 is not exhaustive, as an entity should create collateral to reimburse any future expenses (of course, subject to the recognition conditions). Taking into account the specifics of the entities’ business, various circumstances may arise that will lead to the emergence and recognition of provisions, which in turn requires careful analysis and justification. Conclusions. Based on the study of the conditions for the formation of collateral in the accounting system and the tasks of accounting and management of enterprises, it is advisable to involve qualified specialists and managers to justify the recognition of collateral. Also, the order on accounting policy should reflect information on the types of payments for which a specific provision is formed. It is recommended to improve the wording of the criteria for recognising collateral in accounting, which will facilitate the convergence of National Accounting Standards 11 and IAS 37.